Efektivitas Kegiatan Ecoprint pada Anak Usia 5-6 Tahun: Stimulasi Peningkatkan Kreativitas Anak - Kurlillah, Anis; Yuandana, Tarich (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
The low creativity of early childhood children at TK Negeri Pembina Bangkalan is caused by teacher-dominated learning, monotonous learning materials, and the use of tools and equipment that are less engaging. Additionally, classroom activities are not interesting and do not involve environmental resources. The purpose of this study was to improve the creativity of children aged 5-6 years through ecoprint activities at TK Negeri Pembina Bangkalan. This study employed an experimental method with a Pre-Experimental Design (Non-Designs), specifically using the One Group Pretest-Posttest Design. The population of this study consisted of all children in Group B at TK Negeri Pembina Bangkalan, totaling 33 children, with the sample also consisting of 33 children. Data collection methods included observation, interviews, and documentation. Based on the results of the analysis conducted through the pre-test, treatment, and post-test stages, the findings on the effectiveness of ecoprint techniques in developing creativity in children aged 5-6 years at TK Negeri Pembina Bangkalan showed that in the pre-test, 100% of children were categorized as